A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed - Strümpher, Werner P.; Scholtz, Clarke H. (Zootaxa, 2019)
Phoberus ntlenyanae Strümpher, new species is described from Lesotho and South Africa and is placed in the southern African Phoberus caffer group of species. The P. caffer species group is redefined to include the new species. One taxonomic status change is proposed: Phoberus lilianae (Scholtz, 1980) from the Eastern Highlands of Zimbabwe and the eastern escarpment of South Africa is elevated to species level. Phoberus caffer (Harold, 1872) is recorded for the first time from Eastern Cape and North West Province of South Africa. A key is provided for the identification of the members of the group. Photographs illustrate the species, and a map shows their geographical distributions. [Zoobank URL: urn:lsid:zoobank.org:act:0CB1BAD0-F9C2-4303-B746-487BCADF0D07]